2021
DOI: 10.1186/s10194-021-01287-7
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric and cognitive comorbidities of persistent post-traumatic headache attributed to mild traumatic brain injury

Abstract: Objective To investigate the association of psychiatric and cognitive comorbidities with persistent post-traumatic headache (PTH) attributed to mild traumatic brain injury (TBI). Methods A total of 100 patients with persistent PTH attributed to mild TBI and 100 age- and gender-matched healthy controls free of mild TBI were enrolled between July 2018 and June 2019. Quality of sleep was evaluated using the Pittsburgh Sleep Quality Index, while sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 34 publications
(54 reference statements)
0
28
0
1
Order By: Relevance
“…The study design has been described in detail elsewhere [ 2 , 18 ]. In brief, 100 patients with persistent post-traumatic headache and 100 age- and gender-matched healthy controls were enrolled.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study design has been described in detail elsewhere [ 2 , 18 ]. In brief, 100 patients with persistent post-traumatic headache and 100 age- and gender-matched healthy controls were enrolled.…”
Section: Methodsmentioning
confidence: 99%
“…Conditions associated with persistent post-traumatic headache were evaluated using the following self-report instruments: the 19-item Pittsburg Sleep Quality Index (PSQ-I) to evaluate quality of sleep and the 14-item Hospital Anxiety and Depression Scale (HADS) to screen for anxiety and/or depression [ 20 , 21 ]. The range of the scales and interpretation of the results in the present study populations have been described elsewhere [ 18 ]. In addition, the presence and severity of cutaneous allodynia was assessed using the 12-item Allodynia Symptom Checklist (ASC-12) [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A retrospective observational study of 122 athletes with a mean age of 19 years found that PTH was associated with worse performance in overall cognitive, memory, attention, and processing tests adjusting for baseline cognitive function and other post-concussion symptoms [136]. In a case-control study of 100 patients with persistent PTH attributed to mild TBI and 100 healthy controls without a history of TBI, PTH was associated with increased risk of poor sleep quality (85 vs 42%), anxiety (52 vs 8%), depression (42 vs 2%), and mild cognitive impairment assessed with the MoCA (27%) [137]. However, the study did not include participants with mild TBI without PTH [137].…”
Section: Post-concussion Symptomsmentioning
confidence: 99%
“…In a case-control study of 100 patients with persistent PTH attributed to mild TBI and 100 healthy controls without a history of TBI, PTH was associated with increased risk of poor sleep quality (85 vs 42%), anxiety (52 vs 8%), depression (42 vs 2%), and mild cognitive impairment assessed with the MoCA (27%) [137]. However, the study did not include participants with mild TBI without PTH [137]. The observed association between PTH and sleep disturbances is consistent with prior studies and contributes to worse performance on memory testing [136,138].…”
Section: Post-concussion Symptomsmentioning
confidence: 99%